PENGARUH JAMUR Gliocladium sp. DAN BAKTERI Pseudomonas fluorencens DALAM MENEKAN PERKEMBANGAN PENYAKIT LAYU FUSARIUM PADA TANAMAN PISANG MAS (Musa Paradisiaca L.) HASIL KULTUR INVITRO - Etti Siti Hikmawati; Anis Shofiyani; Bambang Nugroho (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2015)
The objective of the study is to determine the potence of natural agent, a mmushroom of Gliocladium sp. and bacterium Peudomonas fluorencens in resisting against the withering disease (Fusarium Oxysporum f.sp. Cubense) and their effect to the growth of the in-vitrocultured banana plant (Musa paradisiaca L). Thiswas conducted in the experimental farm of Agriculture Faculty, University of Muhammadiyah Purwokerto, in the period of June to December 2013.This research is a single experiment using Randomized Completely Block Design. The treatment was the administration of Gliocladium sp. In three different doses of 10 g/polybag (G1),20 g/ polybag (G2), 30 g/ polybag (G3), and the giving of Pseudomonas fluorencens inthree different dosage of10 ml/l water/ polybag (PF1),20 ml/l water/polybag (PF2) and 30 ml/l water/polybag(PF3) and one control group of no treatment (K0).Based on the result of data analysis, it is proved that the treatment of natural agents of Gliocladiumsp and Pseudomonas fluorencenshas induced the plants resistance against the withering disease of FusariumOxysporumf.sp. Cubense in the banana, as it is indicated bythe increase of phenol compounds, i.e. glychoseda, saponin, and thanin. However, the treatment has no significant effect on the plant growth either on their leaves or their stalk diameter.